2005
DOI: 10.1029/2004gb002315
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of experimental warming on ecosystem carbon processes in a tallgrass prairie

Abstract: [1] This study was conducted to examine direct and indirect impacts of global warming on carbon processes in a tallgrass prairie in the U.S. Great Plains. Infrared radiators were used to simulate global warming, and clipping was used to mimic hay mowing. Experimental warming caused significant increases in green biomass in spring and autumn and total biomass in summer on most of the measuring dates. Green aboveground biomass showed positive linear correlations with soil temperature in spring and autumn whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
242
5
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(274 citation statements)
references
References 75 publications
(104 reference statements)
19
242
5
3
Order By: Relevance
“…The phenological responses noted in this study were in good agreement with many other similar studies (Arft et al, 1999;Wada et al, 2002;Norby et al, 2003;Xu et al, 2009). The phenological differences caused by warming could benefit gross photosynthesis and plant growth (Norby et al, 2003;Wan et al, 2005). Warming-induced phenological changes would lead to a longer favorable period for plant photosynthesis and growth, resulting in increased leaf area index and green biomass during the growing season.…”
Section: Indirect Warming Effects 421 Indirect Warming Effect Throsupporting
confidence: 80%
“…The phenological responses noted in this study were in good agreement with many other similar studies (Arft et al, 1999;Wada et al, 2002;Norby et al, 2003;Xu et al, 2009). The phenological differences caused by warming could benefit gross photosynthesis and plant growth (Norby et al, 2003;Wan et al, 2005). Warming-induced phenological changes would lead to a longer favorable period for plant photosynthesis and growth, resulting in increased leaf area index and green biomass during the growing season.…”
Section: Indirect Warming Effects 421 Indirect Warming Effect Throsupporting
confidence: 80%
“…Third, other studies showed that warming stimulated mineralization (Melillo et al 2002;Rustad et al 2001;), increased plant nutrient uptake and use efficiency (Sardans et al 2008). Similarly, observed increased mineralization and plant nutrient uptake are likely mechanisms leading to stimulated NPP in this study Wan et al 2005). On the other hand, our measurement showed that leaf-level photosynthesis of four dominant species increased significantly in spring, decreased in early fall, and did not change in summer and late fall under warming in comparison with that in control (Zhou et al 2007a).…”
Section: Npp and Its Responses To Climate Warmingcontrasting
confidence: 37%
“…Thus, biofuel feedstock production in the US Great Plains may not be C-negative or help offset atmospheric C buildup due to anthropogenic activities. Owensby et al 2006;Wan et al 2005). As a result, net ecosystem production was positive and the amount of soil C loss was less than the amount of C in the removed biomass in the warming and clipping treatment.…”
Section: Impacts Of Biofuel Feedstock Harvest On Ecosystem Carbon Balmentioning
confidence: 78%
See 1 more Smart Citation
“…Warming directly affects plant growth and shifts in plant species across a range of tundra ecosystems (Walker et al 2006;Elmendorf et al 2012). Several studies indicate that plant aboveground net primary production (ANPP) has variable responses to warming in arctic and alpine regions, with reported increases, decreases, or no change (Houborg and Soegaard 2004;Wan et al 2005;Klein et al 2007;Post and Pedersen 2008). Wania et al (2009) modeled strong increases in Arctic annual NPP using a dynamic global vegetation model (DGVM).…”
Section: Vpm Model Simulationmentioning
confidence: 99%